Case Report: Palliative chemotherapy with gemcitabine and carboplatin for carcinoma of unknown primary with metastasis in a cat - Park, Hyeon-A; Kim, Keon; Choi, Chang Hyeon; Ro, Woong-Bin; Lee, Chang-Min (Frontiers in Veterinary Science, 2026)
Carcinoma of unknown primary (CUP) is a metastatic carcinoma in which the primary tumor site cannot be identified using standard diagnostics, including imaging, histopathology, and immunohistochemistry (IHC). In human medicine, CUP represents the sixth to eighth most prevalent form of cancer, making up about 2.3 to 5% of new cancer diagnoses. It is associated with a poor prognosis and is primarily managed with palliative chemotherapy. However, veterinary research on CUP, particularly in cats, is limited, with few reported cases. A 7-year-old spayed female Domestic Shorthair cat presented with vomiting and anorexia. Computed tomography (CT) revealed multiple masses in the abdomen, liver, and kidneys, with mild sternal and splenic hilar lymphadenopathy. Samples for histology and IHC were taken with ultrasound-guided Tru-Cut needle. The result was consistent with carcinoma of unknown primary. Given the extensive metastases and poor prognosis, a palliative approach focusing on disease stabilization and symptom management was selected. The cat was treated with gemcitabine and carboplatin, showing a positive response and maintaining quality of life for four months. Hematologic side effects, including non-regenerative anemia and neutropenia, were manageable with supportive care. This case suggests that gemcitabine-carboplatin may offer a viable palliative chemotherapy option for CUP in feline patients with non-resectable tumors. Further studies on the use of this protocol in various feline carcinomas are warranted.